Estrutura populacional e diversidade genética em mandioca de mesa da região urbana de Maringá, Paraná - Costa, Tiago Ribeiro da (2010)
Cassava, a species originally from Central region of Brazil, has great importance upon feed of several people over tropical countries. Most of tuberous root production is obtained by plantation systems called "backyard plots", where it is found great genetic variability but it is under the risk of dilution due to selection and exchanges of more attractive accessions among the producers and the accelarated urban growth, especially in Maringá city, Paraná. Therefore, the present study had the objective to evaluate the populational structure and genetic variability among 66 sweet cassava accessions collected in the urban region of Maringá, using molecular markers of microsatellite type. The data obtained were evaluated through methodologies based on genetic distances and probabilistic models for populational structure analyses, whereas through genetic diversity indexes and allelic frequencies, genetic diversity indexes were obtained (Ht, Ho, PIC, %polymorphism and number of alleles) for each evaluated locus, as well as the genetic similarity estimatives among the accessions. All loci evaluated were polymorphic and in average were highly heterozygotic. The number of alleles/locus was considered low, which is another evidence about the limited genetic base due to exchange of accessions and reduced number of ancestors in the population. All markers were considered as medium informative, according to their respective PIC value, in general, the evaluated loci showed considerable genetic diversity with average of 0.5076 and peak of 0.5707 for locus GA 140. Among the most divergent accessions, we could point out BGM 17, 20, 51 and 95; whereas the most similar ones were BGM 25, 33, 37, 59 and 214, because of their high ocurrence in the respective combinations. Accessions BGM 30 and BGM 31 were considered duplicates. Since breeding programs are searching for superior segregants, the hybrid combinations BGM 51 x BGM 296, BGM 95 x BGM 222 and BGM 20 x BGM 12 are recommended. The results from populational structure revealed the formation of two groups, being them better observed by probabalistic methods. The 13 microstatellite evaluated loci have satisfactory characterized sweet cassava accessions in Maringá, regarding to their populational structure and genetic diversity, verifying high genetic variability among the analyzed accessions.